Attending physicians believe that hospitalized patients are treated at the appropriate level of care: A qualitative study. (1st October 2016) - Mauritzon, Ingela Christina; Blom, Mathias; Borna, Catharina; Ivarsson, Kjell
Abstract: The purpose of this paper is to investigate the appropriateness of hospitalized patients' level of care as assessed by their treating physicians. The study was conducted as a qualitative study, based on a questionnaire. The study suggests that physicians generally believe that patients who occupy in-hospital beds are cared for at the appropriate level of care. It is worth to note that a relatively large fraction of patients have had their medical needs attended to, but remain hospitalized while waiting for municipal action. Successful downsizing of in-hospital bed-capacity assumes that either a segment of patients who are inappropriately hospitalized exists and could be identified, or that viable alternatives to in-hospital care exist and are available. The results of the present study argue against the first statement. However, we have identified a segment of patients who experience an unnecessarily long in-patient length of stay due to waiting times for municipal action and other post-discharge follow-up measures. Alternatives to in-hospital care which deserve further attention are supporting services in the outpatient setting.